Hypoxic exposition influence in lengthening performance indicators improvement after intermittent hypoxic training - Nakamoto, F. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The persistence of the enhanced performance endurance capacity obtained with intermittent hypoxic training (IHT) is a topic of extensive debate. Methods to lengthen positive effects of IHT should be studied. The aim of this study is to investigate the influence of intermittent hypoxic exposition (IHE) following IHT on lengthening its benefits. Methods: Twenty well-trained runners (WTR) were assigned to either a hypoxic/hypoxic (HH) group (n = 9), a hypoxic/normoxic (HN) group (n = 6), or a normoxic/normoxic control (C) group (n = 5). Into their usual normoxic training schedule, athletes included two weekly training sessions, performed either in normoxia [C group, inspired O2 fraction (FIO2) = 20.9%] or in normobaric hypoxia (both HH and HN groups, FIO2 = 14.5%), for 6 wk. Following the 6th wk, only HH subjects were exposed to normobaric hypoxia during rest, for 60 min, twice a wk for 4 wk (IHE). The athletes in all groups continued their normal training program in normoxia during the study. Lactate threshold velocity (LTv), 1st and 2nd ventilatory threshold velocities (1VTv and 2VTv), running time to exhaustion (Tlim), maximal oxygen uptake (VO2max) and resting hematological (HT) status were measured before IHT (Pre IHT), after IHT (Post IHT), and after IHE (Post IHE) in all athletes. Results Results: show increase (p<0.05) in VO2max values, LTv, 1VTv, 2VTv and Tlim in both HH and HN groups (Pre IHT x Post IHT values) in normoxia. The C group displayed no improvements. No significant changes were observed in all groups concerning Post IHT x Post IHE values. HT values were unaltered during the study. Discussion: Successful results were obtained from IHT in WTR. Similar results had been found in competitive runners (Dufour et al., 2006). However, IHE procedures adopted in this study were not able to lengthen the adaptations of IHT, probably due to their low frequency or intensity. It`s known that IHE produces physiologic adaptations and enhancement in endurance performance at sea level (Katayama et al, 2004; Bonetti et al., 2009). Once the purpose of our study was not eliciting further changes following IHT, it was thought that this amount of IHE could be enough to increase the persistence of IHT benefits. We either need more athletes participating in the study or a different IHE approach, which might lengthen the benefits of IHT.